Application of domestic cloud simulation software CloudLPS for liquid pipelines - Junfang WANG; Bo YU; Yaping LI; Danfu CAO; Hongmei YU; Junhua GONG; Qing YUAN; Yujie CHEN; Yue XIANG (You-qi chuyun, 2023)
The Cloud-based Liquid Pipeline Simulator(CloudLPS) is a universal liquid pipeline simulation software with completely independent intellectual property rights in China. Herein, its applications are introduced. Its operation processes from pipeline network modeling and simulation calculation to result viewing are elaborated based on a specific case. Then, calculations are performed with CloudLPS for various operating conditions, including steady-state transportation, transient water hammer, and alternating transportation of cold and hot oil, after which the results are compared with those obtained from the foreign commercial software SPS and TLNET, making the discovery that the CloudLPS has comparable accuracy in terms of hydrodynamic and thermal simulations. Subsequently, CloudLPS is applied to solve practical pipeline problems such as normal-temperature transportation, heated transportation, and alternating transportation of cold and hot oil. By comparing the results of these practical applications with the field data, it is proven that the CloudLPS can meet the requirements of the actual engineering calculations. Finally, the two special features of CloudLPS, including visual control logic construction and energy consumption optimization, are presented. The results of this paper indicate that CloudLPS is of great competence in hydrodynamic and thermal simulations, logic control, and energy consumption optimization.